On metrization of the space Dα[0, ∞) - Banys, Rimas (Lietuvos matematikos rinkinys, 2001)
A complete metric on the function space Dα[0, ∞) , which is a subspace of the space Dα[0, ∞) of functions without discontinuities of the second kind, is constructed. This metric converts Dα[0, ∞) into a complete separable metric space. It is a modification of a metric on Dα[0, 1) introduced by Woodroofe, and is stronger than the well-known metrics on Dα[0, ∞). Conditions for compactmess of the subsets of Dα[0, ∞) are given.